Steroidal Alkaloids as an Emerging Therapeutic Alternative for Investigation of Their Immunosuppressive and Hepatoprotective Potential - Jan, Naeem U.; Ahmad, Bashir; Ali, Safdar; Adhikari, Achyut; Ali, Amjad; Jahan, Azra; Ali, Abid; Ali, Hamid (Frontiers in Pharmacology, 2017)
The compounds, sarcovagine-D, alkaloid-C and holaphylline isolated from Sarcococca saligna were found to possess immunosuppressive activities. These compounds were characterized for in-vitro inhibition on human T-cells proliferation and IL-2 production. The compounds showed significant immunosuppressive effect on IL-2 production as well as on phytohemagglutinin stimulated T-cell proliferation in a dose dependent manner. Of all the tested compounds holaphylline was found to be less toxic and safe. These compounds were then evaluated for their in-vivo hepatoprotective potential against CCl4, in which alkaloid-C and holaphylline showed markedly reduced liver inflammation and biochemical parameter (ALT, AST, and ALP) of liver injury. The decrease in the activity of hepatic antioxidant enzyme (SOD) was significantly prevented by holaphylline, likewise gradually the levels of MDA and GSH were also normalized compared to silymarin. The CCl4 induced inflammation and necrosis around the central vein of liver was reduced by sarcovagine-D, alkaloid-C and holaphylline, to 8%, 4% to 1% respectively as assessed by histopathology, thus having better hepatoprotective effect compared to positive control. Steroidal alkaloids attenuated the inflammation of liver around the injured central vein region by down regulating the CCl4 induced activation of hepatic macrophages as well as their number respectively. Therefore, the in-vitro and in-vivo results suggest that steroidal alkaloids from Sarcococca saligna could be excellent immunosuppressive and hepatoprotective agents.